Factors Affecting the Domestic Price of Rice in Indonesia - Hermawan, Wawan; Fitrawaty, Fitrawaty; Maipita, Indra (Universitas Negeri Semarang, 2017)
This study aims to determine the factors that have dominant influence to domestic prices of rice. Ordinary Least Square is used to run model with time series data from BPS. The results of the study we found that domestic rice production and the exchange rate have negative effect on domestic rice prices, in contrast the international rice price and the level of income per capita. Domestic production of rice and international prices of rice do not significantly affect domestic prices of rice, while the exchange rate and per capita income significantly affect domestic prices of rice respectively at the alpha level of 10 and 1 percent. Per capita income is a the greatest influence on the formation of domestic prices of rice by the estimated coefficient of 3.5985. This condition also describe the level of society's dependence on rice consumption. The high of difference of domestic price of rice with the international rice prices can be detrimental to the community while providing a strong emphasis on increasing imports of rice as well as trigger the illegal market.